INVESTIGATION OF THE EFFECTIVENESS OF THE PLAYFUL COMPETITION IN ADOLESCENT FOOTBALL PLAYERS - Bucz, Bence; Horváth, Tamás; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2024)
Games are one of the most effective educational methods. Thanks to the game and the competitive situation, we can avoid monotonous work and motivate the child. In our research, we were interested in how the players’ performance changes due to the competitive situation. We hypothesized that speed and agility would be more effective if the competitive method were used. U-16 football players took part in the study. Our results showed that in both cases, speed and agility improved when we used the playful method. In this case, the playful method was to create a competitive situation. When measuring speed, 81% of players achieved better results when we created a competitive situation. When testing agility, 75% of the players performed better with the player method.